Le magistrat français au carrefour de deux systèmes juridiques : un double rôle dans la distribution de la justice indigène à Madagascar - Fara Aina Razafindratsima (Clio@Themis)
From 1896 to 1960, Madagascar remained under French domination. The colonizer was to assure the administration of justice. French policy consisted in introducing into the judiciary organization French judges whose task it was to bring to the country Western values, thus playing an important role in colonial domination. However, at the same time, they were obliged to respect certain traditional native institutions. So, the judge has to accomplish a dual mission : to assure the protection of their customary law to the indigenous population, and to implement the law of metropolitan France to that indigenous population with a view to assimilate them to the French culture.